A TEST OF QUANTUM ELECTRODYNAMICS IN THE REACTION E+E- -]GAMMA-GAMMA(GAMMA) - Adriani, O; Aguilarbenitez, M; Ahlen, S; Akbari, H; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; et al. (1992)
We have measured the total and differential cross sections of the reaction e+e- → γγ(γ) at center-of-mass energies around 91 GeV, with an integrated luminosity of 14.2 pb-1. The results are in good agreement with QED predictions. We set lower limits, at 95% confidence level, on the QED cutoff parameters of Λ+ > 139 GeV, Λ- > 108 GeV and on the mass of an excited electron of me* > 127 GeV. We searched for Z0 rare decays with photonic signitures in the final state. Upper limits, at 95% confidence level, for branching ratio of Z0 decaying into π0γ/γγ, νγ and γγγ are 1.2 × 10-4, 1.8 × 10-4, 3.3 × 10-5 respectively. © 1992.